Consumer perceptions of product and service quality; a case study of AS Photography's management information system - Tafsiruddin, Muh; Saefullah, Aep; Noor, M.Arief; syafran, syafran; Nurhakim, Rahman (Institute of Computer Science (IOCS), 2024)
Management information systems are an important part of AS Photography in managing business processes effectively and efficiently to improve the quality of products and services. The purpose of this study was to analyse the perceptions of AS Photography Kuningan consumers regarding information system management on product and service quality. This research uses a phenomenological approach in order to focus on individual perceptions, namely consumers of AS Fotografi Kuningan as participants by conducting semi-structured interviews. Qualitative data analysis techniques were applied using NVivo assistance. The results showed that the management information system has a positive impact on the quality of products and services at AS Fotografi Kuningan. There are six elements that can affect the quality of photography services, namely product quality, service quality, consumer value-added experience, the influence of the AS Photography Management Information System, and consumer use of the SIM application. The function of the Management Information System helps in AS Fotografi Kuningan, namely managing customer data, organising work agenda schedules, managing inventory of goods, managing company cash flow, performance analysis, project management, marketing and promotion, data security, team collaboration, increasing operational efficiency. The implications of this research indicate that Management Information Systems can be an effective tool to improve the quality of photography products and services. The management of AS Kuningan Photography needs to utilize SIM optimally to improve competitiveness in the photography industry